Breaking barriers: exploring female-specific health challenges affecting performance in an elite multisport training environment - de Jager, E.; Willemsen, M.; Kempe, M.; Janssen, I. (Journal of Science and Medicine in Sport, 2024)
Objectives Female-specific issues, such as breast injuries, pelvic floor dysfunctions, saddle sores, and menstrual symptoms, can significantly impact female athletes. This study examined the prevalence, perceived impact on performance, and role of the support staff in addressing and managing these issues in elite athletes based at a multisport training centre.